2018
DOI: 10.1159/000490773
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Full-Fluence and Half-Fluence Photodynamic Therapy for Chronic Central Serous Chorioretinopathy

Abstract: Purpose: To evaluate the efficacy and safety of full-fluence photodynamic therapy (PDT) and half-fluence PDT in chronic central serous chorioretinopathy (CSC). Procedures: A retrospective review of CSC patients treated with full-fluence or half-fluence PDT for 12 months was performed. Best-corrected visual acuity (BCVA), central macular thickness (CMT), neural retinal thickness, subfoveal choroidal thickness (SFCT), resolution of subretinal fluid (SRF), and incidence of retinal pigment epithelium (RPE) atrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
(52 reference statements)
0
9
0
3
Order By: Relevance
“…The combination therapy with PDT was more likely to result in macular atrophy than that with anti-VEGF alone [ 20 ]. Son et al compared half-dose versus full-dose PDT for CSC and found no difference in macular atrophy at three years between the two groups [ 21 ]. We previously reported that PDT monotherapy was administered for PCV with a three-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The combination therapy with PDT was more likely to result in macular atrophy than that with anti-VEGF alone [ 20 ]. Son et al compared half-dose versus full-dose PDT for CSC and found no difference in macular atrophy at three years between the two groups [ 21 ]. We previously reported that PDT monotherapy was administered for PCV with a three-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies on the BCVA after halftime PDT treatments for chronic CSC with a posttreatment of more than two years [15,[27][28][29][30][31][32][33]. Although there were several studies that followed the retinal sensitivity for a long period [12,14,16,23,[34][35][36][37][38], most of the follow-up period was at most one year.…”
Section: Discussionmentioning
confidence: 99%
“…If the treatment spot is smaller than expected, CSC may be left untreated, resulting in treatment failure. By contrast, oversized treatment may result in a larger area of damage to the retina, RPE, and choroid than necessary, which may lead to unnecessary loss of visual function [1516]. Several complications associated with PDT have been reported, such as choroidal ischaemia, choriocapillaris hypoperfusion, persistent RPE atrophy, and secondary CNV [17].…”
Section: Discussionmentioning
confidence: 99%